The Effectiveness of Training on Improving the Ability of Health Cadres in Early Detection of Stunting in Toddlers - Tampake, Rina; Arianty, Ros; Mangundap, Selvi A .; Emy, Baiq; Sasmita, Hanum (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This study aimed to determine the effectiveness of training in improving health cadres’ ability in early detection and risk factors of stunting in toddlers. METHODS: The research method used was a quasi-experimental non-randomized pre- and post-test only control design. The independent variable was cadre training. The training was conducted through learning activities on health cadres using lecture method, question and answer method, and brainstorming accompanied by training booklets/modules and demonstrations. The dependent variable was knowledge, attitudes, and skills in detecting stunting and risk factors for stunting in children under-five. There were 53 health cadres as samples scattered in the Tomini Community Health Center with the purposive sampling technique. The data analysis technique used was a parametric statistical paired sample t-test. RESULTS: Training of health cadres effectively increased health cadres’ ability to detect stunting and risk factors for stunting in children under-five. The different test results for each variable that showed the pre-post-test p-value for knowledge, attitudes, and health cadres’ skills were 0.000, smaller than the significance level of 0.05 (p < 0.05). Besides, the mean score of each variable obtained after training for health cadres was more significant than before training, including knowledge 17.392 >12.264, attitudes 33.603 >27.226, and skills 90.019 >62113. Those are means that cadres’ training effectively increased the knowledge, attitudes, and skills of health cadres in detecting stunting and risk factors for stunting in children under-five. CONCLUSION: Training of health cadres effectively increases the knowledge, attitudes, and skills of health cadres about early detection and risk factors of stunting in the working area of Tomini Public Health Centre, Parigi Moutong Regency.